2017
DOI: 10.1371/journal.pone.0169216
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Self-Reported Sleep Quality with Circulating Interferon Gamma-Inducible Protein 10, Interleukin 6, and High-Sensitivity C-Reactive Protein in Healthy Menopausal Women

Abstract: IntroductionSleep disturbance is very common in menopausal women and poor sleep quality has been linked to systemic inflammation. However, the impact of poor sleep quality on health outcomes of menopausal women remains unclear. This study evaluated the relationships between sleep quality and inflammation in menopausal women.Participants and designThis cross-sectional study enrolled 281 healthy women aged 45 to 60 years. The Pittsburgh Sleep Quality Index (PSQI) was used to measure quality of sleep. Multiplex a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 57 publications
2
14
0
Order By: Relevance
“…Physical activity is also a protective factor against the development of depressive disorders (Strawbridge et al, 2002). Sleep deprivation has been increasingly linked to elevated CRP levels (Meier-Ewert et al, 2004) as has poor quality of sleep (Huang et al, 2017). Moreover, disruptions in sleep have also been linked to more severe presentations of depression (Tsuno et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Physical activity is also a protective factor against the development of depressive disorders (Strawbridge et al, 2002). Sleep deprivation has been increasingly linked to elevated CRP levels (Meier-Ewert et al, 2004) as has poor quality of sleep (Huang et al, 2017). Moreover, disruptions in sleep have also been linked to more severe presentations of depression (Tsuno et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…81 In summary, primary sleep disorders become more prevalent in older age, affecting > 53% of postmenopausal women. [103][104][105] Moreover, poor sleep in perimenopausal/postmenopausal women is associated with inflammation, 106 cardiovascular and metabolic disease, [107][108][109] and mood disorders. Understanding the evolution of sleep across a woman's life span may lead to effective therapies that affect women's health and quality of life.…”
Section: Sleep Changes Related To Mood Disordersmentioning
confidence: 99%
“…Previous studies investigated the effects of sleep disorders such as obstructive sleep apnea [20,21] and insomnia [22] on hs-CRP levels. Several studies have evaluated the association between sleep characteristics and hs-CRP level among the general population [6,9,13,23]; the results, however, derive from mainly western population or are conservative in sample size [24][25][26][27][28]. A 2009 study carried out by the Organization for Economic Cooperation and Development reported that Koreans ranked at the bottom of 18 countries for sleep time; a nationwide study found that nearly 20% of Korean adults were affected by insomnia, reflecting an increase from 2002 survey [29,30].…”
Section: Introductionmentioning
confidence: 99%